2021
DOI: 10.3389/fphys.2021.712593
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Survey of the Moth PBP/GOBP Clade in Bombyx mori: New Insight into Expression and Functional Roles

Abstract: We studied the expression profile and ontogeny (from the egg stage through the larval stages and pupal stages, to the elderly adult age) of four OBPs from the silkworm moth Bombyx mori. We first showed that male responsiveness to female sex pheromone in the silkworm moth B. mori does not depend on age variation; whereas the expression of BmorPBP1, BmorPBP2, BmorGOBP1, and BmorGOBP2 varies with age. The expression profile analysis revealed that the studied OBPs are expressed in non-olfactory tissues at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 113 publications
2
8
0
Order By: Relevance
“…These results support a potential function of sex pheromone component detection by H. cunea females. Similar results were also reported in other moths, such as A. lepigone , Bombyx mori , C. sasakii , Cydia pomonella , Grapholita molesta, H. armigera , and P. xyllostella 23,51,52 . In fact, expression of HcunGOBPs2 in the antennae regardless of sexes were shown approximately five times higher than that of HcunGOBPs1 , suggesting that HcunGOBPs2 may play more vital roles in the perception of female sex pheromones than does HcunGOBPs1 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results support a potential function of sex pheromone component detection by H. cunea females. Similar results were also reported in other moths, such as A. lepigone , Bombyx mori , C. sasakii , Cydia pomonella , Grapholita molesta, H. armigera , and P. xyllostella 23,51,52 . In fact, expression of HcunGOBPs2 in the antennae regardless of sexes were shown approximately five times higher than that of HcunGOBPs1 , suggesting that HcunGOBPs2 may play more vital roles in the perception of female sex pheromones than does HcunGOBPs1 .…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were also reported in other moths, such as A. lepigone, Bombyx mori, C. sasakii, Cydia pomonella, Grapholita molesta, H. armigera, and P. xyllostella. 23,51,52 In fact, expression of HcunGOBPs2 in the antennae regardless of sexes were shown approximately five times higher than that of HcunGOBPs1, suggesting that HcunGOBPs2 may play more vital roles in the perception of female sex pheromones than does HcunGOBPs1. Surprisingly, there was a trace amount of expression of HcunGOBP2 and Hcun-GOBP1 in the male thoraxes, suggesting that a possible metabolic regulation occurs at GOBP levels in the male thoraxes (and/or fat bodies) or alternative functions for these proteins other than olfaction (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…After the activation of the chemosensory receptors, odorant degrading enzymes (ODEs) rapidly degrade the odorants [ 10 ]. However, other studies have demonstrated that the expression of odorant-binding proteins in other tissues such as the salivary glands, fat body, or midgut may be associated with alternative physiological functions in the insect [ 11 , 12 , 13 ]. Some OBPs , for instance, have been found to relate to innate immunity, pesticide resistance, and anti-inflammation [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…OBPs are currently considered to have multiple functions, especially when OBPs are expressed in non-olfactory tissues. For instance, a new study in Bombyx mori showed that the investigated OBPs are expressed in non-olfactory tissues at different developmental stages, strongly indicating that these OBPs have multiple functions in addition to olfactory functions [ 12 ]. Through Western blot analysis and immunofluorescence localization, AaegOBP22 was found to be expressed in male sex organs in Aedes aegypti , and to have characteristics of selective binding with various ligands [ 13 ].…”
Section: Introductionmentioning
confidence: 99%